Obudź w sobie dobrego cżłowieka (Poland, 2009)
A story about people who need each other. The re-socialization program called "Bona" started in 1998 when the principal of "Zameczek" Social Assistance House for disabled Children in Lubliniec asked the administration of the penitentiary in his town, if women who are in prison could take care of the children placed in that institution.
Verzio Film Festival Submission
Keywords: Documentary films